THE STUDY OF THE STRUCTURAL ORGANIZATION OF SERVICEMEN PERSONALITY WITHIN THE FRAMEWORK OF PSYCHOLOGICAL SUPPORT AT THE STAGE OF THEIR ADAPTATION - Мозговий, Віктор Іванович (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2018)
The article at analyzes peculiarities of the structural organization of servicemen personality regularservice at the stage of their adaptation to military activity.The criteria for identifying and researching the personal level of the neuromuscular stability of servicemen,their susceptibility to suicidal behavior, emotional breakdown and the presence of their asocial settings,which influences the formation of a risk group and a group of additional attention, are identified.The question of the effectiveness psycho-corrective algorithm application measures of psychologicalsupport at the stage of regular service soldier’s adaptation, which includes 5 stages: psychodiagnostic examination, psycho education, training sessions, individual consultations and conducting of repeated psychodiagnostic examination of servicemen. At each stage, the complex influence on emotional regulatory and communicative spheres of a soldier personality is realized.The specific personality factors that are sensible to the influence of psychological support measures arerevealed. These factors are the main focus of a military psychologist work during the conduct of psychological support for servicemen at the stage of adaptation to military service. The effectiveness of the proposed system of psychological support and application of the corresponding algorithm of measures at the stage of servicemen adaptation to the requirements of military service is confirmed, as a result of which there is an increase of their psychological stability and formation of identity with military service personnel. The difference in the personal structure among different groups of military personnel was revealed. The focus of further psychologists work with different groups of servicemen during the period of their adaptation is determined.